Técnicas basadas en la terapia racional emotiva conductual para disminuir comportamientos agresivos en los estudiantes de sexto año paralelo “A” de la escuela de educación básica Lauro Damerval Ayora n°2 de la ciudad de Loja, 2014-2015 - Gutierres Pazmiño, Adrian Israel (2016)
In the investigated reality, the aggressive behaviors in the students are one of the most common problematics inside the scholar context, for this reason as an objective was proposed, the execution of a psycho-educative program to reduce the aggressive behavior. The study was descriptive, cross sectional, with a quasi-experimental design. The methods used were: analytic, synthetic, deductive, historic and statistic. The A-Q questionnaire by Buss and Perry was applied to a seventeen students sample, that manifested aggressive behaviors in high levels (pretest): Consequently, after the application of the psycho-educative program this value decreased to 5, 88%, According to the Pearson’s correlational coefficient a value of r=0, 52 was reached, In conclusion, the high hostility decreased to low levels, validating the intervention with a positive and moderate correlation.